2020
DOI: 10.1021/acs.jafc.9b08212
|View full text |Cite
|
Sign up to set email alerts
|

Shading Effects on Leaf Color Conversion and Biosynthesis of the Major Secondary Metabolites in the Albino Tea Cultivar “Yujinxiang”

Abstract: Albino became a novel kind of tea cultivar in China recently. In this study, transcriptome and whole-genome bisulfite sequencing (WGBS) were employed to investigate the shading effects on leaf color conversion and biosynthesis of three major secondary metabolites in the albino tea cultivar “Yujinxiang”. The increased leaf chlorophyll level was likely the major cause for shaded leaf greening from young pale or yellow leaf. In comparison with the control, the total catechin level of the shading group was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 58 publications
3
37
0
Order By: Relevance
“…C4H acts as a rate-limiting enzyme in phenylpropanoid biosynthesis and exhibits the same markedly reduced expression levels in the shading treatment group, which may lead to differential accumulation of p -coumaroyl-CoA upstream of flavonoid biosynthesis. In this study, 14 DEPs involved in flavonoid biosynthesis, including CHS, F3H, F3′,5′H, and ANS, were significantly downregulated during the shading period ( Figure 7 ), which was similar to the results reported by Xu et al (2020) . Previous studies have suggested that an inactivating mutation of CHS can lead to decreased flavonoid accumulation in plants ( Li et al, 1993 ).…”
Section: Discussionsupporting
confidence: 88%
“…C4H acts as a rate-limiting enzyme in phenylpropanoid biosynthesis and exhibits the same markedly reduced expression levels in the shading treatment group, which may lead to differential accumulation of p -coumaroyl-CoA upstream of flavonoid biosynthesis. In this study, 14 DEPs involved in flavonoid biosynthesis, including CHS, F3H, F3′,5′H, and ANS, were significantly downregulated during the shading period ( Figure 7 ), which was similar to the results reported by Xu et al (2020) . Previous studies have suggested that an inactivating mutation of CHS can lead to decreased flavonoid accumulation in plants ( Li et al, 1993 ).…”
Section: Discussionsupporting
confidence: 88%
“…Liu et al reported that shade treatment barely impacted the TC content of the light-sensitive albino tea cultivar ‘Yujinxiang’, along with a greater reduction of quercetin and lower reduction of kaempferol [ 35 ]. A decrease in TC content was also observed in the young shoots of the albino tea cultivar ‘Yujinxiang’ under shade treatment [ 38 ]. Different tea cultivars and different growing stages of tea plants, such as plant age, cultivation method (pot culture or field culture), and leaf maturity, are non-negligible factors affecting the responses of tea plants to altered light conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that flavonol profiles were highly associated with characteristics that were related to canopy structure and light interception ( Martínez-Lüscher et al, 2019 ). One of the main flavonoids, catechins, in an albino tea cultivar, significantly decreased with plant shading, which was associated with DNA methylation involved in the flavonoid biosynthesis pathway ( Xu et al, 2020 ). In this study, RSA levels in the upper leaves were also highest for both growth stages ( Figures 5E , F ).…”
Section: Discussionmentioning
confidence: 99%